Comparative Performance Measurement in the Full Electric Vehicle Market - Erhan Demireli; Mert Ural; Üzeyir Aydın (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
In this study, Entropy, WASPAS and MOORA methods, which are multi-criteria decision-making techniques, are used to measure the performance of the best-selling full electric cars in Türkiye as of October 2023 by the Automotive Distributors and Mobility Association using 12 different criteria. The weights of the criteria were calculated with the Entropy method. Then, the electric cars were ranked by evaluating their performance with the WASPAS and MOORA-based methods. In the study, it was concluded that the top three criteria with the highest weights were power (HP), fast charging time and battery capacity, while the top three highest performing electric cars were TOGG T10X V2 Long Range, Volvo XC40 RWD (Single Motor) and Tesla Y Long Range RWD (4x2).